2013
DOI: 10.1007/s12602-013-9125-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Antilisterial Effect of Phosphatidylcholine Nanovesicles Containing the Antimicrobial Peptide Pediocin

Abstract: Encapsulation may provide increased stability and antimicrobial efficiency to bacteriocins. In this work, the antilisterial peptide pediocin was encapsulated in nanovesicles prepared from partially purified soybean phosphatidylcholine. The maintenance of antimicrobial activity and properties of free and encapsulated pediocin was observed during 13 days at 4 °C, and after this period, the encapsulated pediocin retained 50 % its initial activity. The maintenance of the bioactive properties of free and encapsulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…These findings suggest that the stability of bacteriocins against unfavorable environmental conditions can be improved by nanoliposomal formulations, which still remains to be proved by assessing their AMA (Taylor et al, 2007 ). A similar study was reported by de Mello et al ( 2013 ), in which pediocin AcH had been successfully loaded with high (80%) entrapment efficiency, stability, and antimicrobial activity, for at least 13 days, when incorporated into phosphatidylcholine nanovesicles (de Mello et al, 2013 ). However, it must be stated that while the liposome-encapsulated pediocin has been shown to maintain its AMA for a longer period, this activity was lower than that of the free pediocin, which requires further investigations to overcome this issue (de Mello et al, 2013 ).…”
Section: Nanotechnological Approaches Used In Bacteriocin Formulationsupporting
confidence: 68%
See 1 more Smart Citation
“…These findings suggest that the stability of bacteriocins against unfavorable environmental conditions can be improved by nanoliposomal formulations, which still remains to be proved by assessing their AMA (Taylor et al, 2007 ). A similar study was reported by de Mello et al ( 2013 ), in which pediocin AcH had been successfully loaded with high (80%) entrapment efficiency, stability, and antimicrobial activity, for at least 13 days, when incorporated into phosphatidylcholine nanovesicles (de Mello et al, 2013 ). However, it must be stated that while the liposome-encapsulated pediocin has been shown to maintain its AMA for a longer period, this activity was lower than that of the free pediocin, which requires further investigations to overcome this issue (de Mello et al, 2013 ).…”
Section: Nanotechnological Approaches Used In Bacteriocin Formulationsupporting
confidence: 68%
“… Schematic representation showing some of the nanotechnological approaches used in bacteriocin formulations with their associated characters . 35, da Silva Malheiros et al, 2012a ; 41, da Silva Malheiros et al, 2012b ; 46, de Mello et al, 2013 ; 69, Zohri et al, 2010 ; 70, Zohri et al, 2013 ;71, Bernela et al, 2014 ; 72, Chopra et al, 2014 ; 33, Mossallam et al, 2014 ; 80, Thirumurugan et al, 2013 ; 87, Sharma et al, 2012 ; 94, Heunis et al, 2013 ; 95, Heunis et al, 2011 ; 100, Ahire and Dicks, 2015 ; 101, Ahire et al, 2015 . …”
Section: Advantages Of Nanoformulated Bacteriocinsmentioning
confidence: 99%
“…Gram-positive bacteria are inhibited by most bacteriocins. Gram-negative bacteria can be increasingly sensitive to bacteriocins after the use of chelating agents or hydrostatic pressure [205,206]; these techniques can also be synergic enhancing the action of bacteriocins against Gram-positive bacteria [189,207], or even with the use of nanoparticles [208,209] or nanovesicles [210].…”
Section: Bacteriocinsmentioning
confidence: 99%
“…Human epidermal keratinocytes studies showed that these nanoparticles were non-toxic at the concentrations used to inhibit microbial growth. Nisin nanoparticles have been tested against L. monocytogenes and S. aureus with good results [302][303][304], as well as bacteriocin nanovesicles [210] or nanoparticles [208,209] against different pathogens. Zou et al [302] evaluated the prolonged antimicrobial stability of liposome nanoparticles loaded with nisin against L. monocytogenes and S. aureus.…”
Section: Nanoparticles and Nanovesiclesmentioning
confidence: 99%
See 1 more Smart Citation